2021
DOI: 10.3389/fnins.2020.600083
|View full text |Cite
|
Sign up to set email alerts
|

Now You See One Letter, Now You See Meaningless Symbols: Perceptual and Semantic Hypnotic Suggestions Reduce Stroop Errors Through Different Neurocognitive Mechanisms

Abstract: Compelling literature has suggested the possibility of adopting hypnotic suggestions to override the Stroop interference effect. However, most of these studies mainly reported behavioral data and were conducted on highly hypnotizable individuals. Thus, the question of the neural locus of the effects and their generalizability remains open. In the present study, we used the Stroop task in a within-subject design to test the neurocognitive effects of two hypnotic suggestions: the perceptual request to focus only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…The LPC effect might relate to the latter interpretation in that it occurred at a very late stage of processing, i.e., along response execution, and was evident only in the subtractions where the incongruence condition was the minuend. This component further relates to a recent study [54] in which the authors showed the occurrence of a late posterior positivity (LPP), which was enhanced in incongruent rather than congruent and neutral trials.…”
Section: Discussionsupporting
confidence: 75%
“…The LPC effect might relate to the latter interpretation in that it occurred at a very late stage of processing, i.e., along response execution, and was evident only in the subtractions where the incongruence condition was the minuend. This component further relates to a recent study [54] in which the authors showed the occurrence of a late posterior positivity (LPP), which was enhanced in incongruent rather than congruent and neutral trials.…”
Section: Discussionsupporting
confidence: 75%
“…The neurostimulation of other areas of the agency brain network such as the angular gyrus (see, e.g., Khalighinejad & Haggard 2015 ) could clarify whether it leads to changes in the feeling of control and pass rates for different items on the traditional behavioural scales of hypnotic suggestibility. Stimulation of posterior areas could also help prevent possible confounding interpretations of changes in the PFC activity: in fact, despite the inhibition of the PFC was identified as a sign of the reduced DN activity during neutral hypnosis (for a meta-analysis see Landry et al, 2017 ), a greater engagement of PFC was observed when hypnotic suggestions required increased executive control ( Huber et al, 2013 ; Perri et al, 2020 a; Zahedi et al, 2017 , 2019 ), thus suggesting the cognitive flexibility (and not the PFC suppression) as a core aspect of hypnotic abilities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it could be interesting to observe if the stimulation of motor and sensory areas can enhance the responsiveness to the ideomotor and perceptual items. Moreover, because it becomes increasingly evident that the subjective and the behavioural experience reflect different components of hypnotizability ( Acunzo & Terhune, 2021 ; Facco, 2021 ; Hung & Barnier, 2005 ; Perri et al, 2020 a), it is necessary for future studies to adopt also phenomenological measures when investigating the variation of consciousness during hypnosis.…”
Section: Discussionmentioning
confidence: 99%
“…When the sample composition is based on hypnotizability, it is recommended to include medium hypnotizables as well (instead of contrasting high vs. low hypnotizables), as medium hypnotizables form the majority of the general population (33,(72)(73)(74). This will increase the generalizability of the study findings.…”
Section: Do Not Restrict Enrollment To Only High and Low Hypnotizable...mentioning
confidence: 99%